Evaluating the Duration and Continuity of Potential Climate Records From the Allan Hills Blue Ice Area, East Antarctica. Issue 9 (8th May 2018) - Kehrl, Laura; Conway, Howard; Holschuh, Nicholas; Campbell, Seth; Kurbatov, Andrei V.; Spaulding, Nicole E.
Abstract: The current ice core record extends back 800, 000 years. Geologic and glaciological evidence suggests that the Allan Hills Blue Ice Area, East Antarctica, may preserve a continuous record that extends further back in time. In this study, we use ice‐penetrating radar and existing age constraints to map the internal stratigraphy and age structure of the Allan Hills Main Ice Field. The dated isochrones provide constraints for an ice flow model to estimate the age of ice near the bed. Previous drilling in the region recovered stratigraphically disturbed sections of ice up to 2.7 million years old. Our study identifies a site ~5 km upstream, which likely preserves a continuous record through Marine Isotope Stage 11 with the possibility that the record extends back 1 million years. Such records would provide new insight into the past climate and glacial history of the Ross Sea Sector. Plain Language Summary: Ice cores currently provide detailed, continuous records of Earth's climate and atmosphere over the past 800, 000 years. Discrete ice samples with ages up to 2.7 million years have been recovered from the Allan Hills Blue Ice Area, East Antarctica, indicating that the region may preserve a continuous record that extends beyond 800, 000 years. In this study, we use ice‐penetrating radar and an ice flow model to identify an optimal site for a continuous ice core record from the Allan Hills, which may extend over the last 1 million years. Such a long ice core record would help us better understand the fundamental drivers of Earth's climate. Key Points: Ice‐penetrating radar can detect steeply dipping (up to 30‐40 degrees) englacial stratigraphy in blue ice areas Despite steep basal topography, the Allan Hills likely preserves a continuous ice core record back at least 500 ka and possibly back 1 Ma Downstream propagation of stratigraphic anomalies indicates that surface velocities were ~30% of modern values during the last glaciation